Understanding the Corporate Values of Islamic Commercial Banks with the Theory of MM Preposition and David Durand in Capital Structure Theory - Difa Tsaniya Nafhanti; Darmawan Darmawan (Review of Islamic Economics and Finance (RIEF), 2019)
This study aims to understand the value of Islamic public bank companies registered at OJK during 2013-2017. The used approach is the capital structure theory of MM preposition and David Durand. The used analytical method in this study is panel data regression analysis with the Random Effect Model. The study results show that the tax rate, profitability, and cost of capital simultaneously affect Islamic commercial bank companies' value. Partially, tax rates and profitability affect the value of Islamic commercial bank companies. The cost of capital does not affect the value of Islamic commercial bank companies. This study proved that the prevailing MM preposition capital structure theory is MM prepositions without tax in companies based on institutional ownership, especially Islamic commercial banks. This study also succeeded in proving that the theory of David Durand's capital structure was proven. The cost of capital variables become influential when the company is divided into two based on institutional ownership.